2021
DOI: 10.37251/isej.v2i1.124
|View full text |Cite
|
Sign up to set email alerts
|

Description of Science Process Skills of Physics Education Students of Jambi University on Refraction Material on Concave Lenses Using E-Module

Abstract: Purpose of study: This study was conducted to determine the science process skills of physics education students for refraction material on a concave lens. The questions discussed in this study are to describe the basic and integrated science process skills of Jambi University physics education students, what are the obstacles faced when the implementation of the e-module basic physics practicum II is applied, what are the solutions to the obstacles faced. Methodology: This study uses a quantitative appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…The results of the study in this study are in line with research by Izzati with the results of the study that there is an effect of mathematical connections and dispositions on learning outcomes [46]. Similarly, research by Mandur, Sadra, and Suparta has shown that the ability to make connections, representational skills and mathematical arrangements make a significant contribution to the learning of mathematics [47].…”
Section: Resultssupporting
confidence: 88%
“…The results of the study in this study are in line with research by Izzati with the results of the study that there is an effect of mathematical connections and dispositions on learning outcomes [46]. Similarly, research by Mandur, Sadra, and Suparta has shown that the ability to make connections, representational skills and mathematical arrangements make a significant contribution to the learning of mathematics [47].…”
Section: Resultssupporting
confidence: 88%
“…To face the challenges of an increasingly complex era, we need to strengthen human resources in life and career through comparative capabilities, innovative thinking, competitiveness and collaboration [1]- [3]. Learning that prioritizes innovative thinking needs to be improved [4]- [6]. Innovation is closely related to the creative thinking abilities that a person has in various fields [7]- [9].…”
Section: Introductionmentioning
confidence: 99%